Pelatihan Wirausaha Kreatif: Pembuatan Sabun Cuci Piring sebagai Produk Usaha Rumah Tangga di Desa Kuala Indah - Muammar Tanjung; Rizvy Azyura; Suci Haryanti; Siti Ismahani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
This community service activity was carried out in Kuala Indah Village with the aim of improving the skills and economic independence of the community through creative entrepreneurship training in the form of making liquid dish soap. This program was motivated by the socio-economic conditions of the village community, the majority of whom work In the informal sector with uncertain incomes, so that alternative businesses that are easy to do and have economic value are needed. The implementation method of the activity consisted of three stages: socialization, provision of materials, and direct practice of soap making. The results of the activity showed that the community was very enthusiastic in participating in the training and was able to practice the soap making process independently, from mixing the ingredients to packaging the final product. Through this activity, the community gained new knowledge about the ingredients, functions, and benefits of dish soap, as well as opportunities for developing it as a household business. This training successfully improved the skills, motivation, and entrepreneurial spirit of the Kuala Indah Village community, while also opening up opportunities for the formation of independent small businesses that have the potential to improve the family economy